Penerapan Model Pembelajaran Diferensiasi (Differentiated Instruction) untuk Meningkatkan Hasil Belajar Kognitif Siswa pada Mata Pelajaran Biologi - Nurdewiyanti, Nurdewiyanti; Karmana, I Wayan (Biocaster : Jurnal Kajian Biologi, 2025)
The application of innovative learning media can improve students' cognitive learning outcomes on a subject matter. One interesting solution that can be applied is the application of a differentiation learning model (differentiated instruction). This study aims to analyze the application of a differentiation learning model (differentiated instruction) in improving the cognitive learning outcomes of class X students at SMA Negeri 8 Mataram in Biology subjects. This study uses Classroom Action Research (CAR) with data collection techniques in the form of cognitive learning outcome tests. In Cycle I, students' cognitive learning outcomes were 63 and the classical completeness value was 49%, thus in terms of classical completeness it was not yet complete. While the cognitive learning outcomes of students after applying the differentiation learning model in Cycle II were 92 or 87%, students managed to achieve the learning completeness criteria. The overall achievement of the class can exceed the completeness standard and further strengthen the positive impact of the learning approach using the differentiation learning model (differentiated instruction). Thus, it can be concluded that the application of the differentiation learning model (differentiated instruction) contributes significantly to improving the cognitive learning outcomes of class X students in Biology subjects at SMA Negeri 8 Mataram.